2008
DOI: 10.1089/rej.2007.0613
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation in the Elderly Reduces Spontaneous Inflammatory Cytokine Release and Restores T Cell Functions

Abstract: Aging is associated with low-grade inflammation on the one hand and mild zinc deficiency on the other. These conditions contribute to decreased immune functions, resulting in increased incidences of infections and autoimmune diseases. The aim of this study was to give more insight into the question, to what extent is low-grade inflammation caused by zinc deficient status. Here we report the effect of improved intracellular zinc status on low-grade inflammatory activity in 19 healthy elderly subjects. Our exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 47 publications
3
86
0
1
Order By: Relevance
“…Similarly, inducing deficiency in healthy men via zinc restricted diet (4.6 mg/day for 10 weeks) led to reduction of PHA-stimulated IL-2R production [75]. Furthermore, IL-6 production in zinc deficient elderly subjects was increased [76]. These observations were later confirmed via DNA methylation profile characterization, which showed that zinc deficiency induced a progressive demethylation of the IL6 promoter in THP1 cells that correlated with increased IL6 expression [77].…”
Section: Zinc Status and Inflammatory Cytokinesmentioning
confidence: 82%
“…Similarly, inducing deficiency in healthy men via zinc restricted diet (4.6 mg/day for 10 weeks) led to reduction of PHA-stimulated IL-2R production [75]. Furthermore, IL-6 production in zinc deficient elderly subjects was increased [76]. These observations were later confirmed via DNA methylation profile characterization, which showed that zinc deficiency induced a progressive demethylation of the IL6 promoter in THP1 cells that correlated with increased IL6 expression [77].…”
Section: Zinc Status and Inflammatory Cytokinesmentioning
confidence: 82%
“…33 It has further been shown that levels of pro-inflammatory cytokines in elderly are increased during zinc deficiency and that this can be reversed through zinc supplementation. [34][35][36] In contrast, the production of TNF-a and IL-6 can be increased through zinc supplementation in PBMC. 4,7 This study indicates that TNF-a and IL-6 production is decreased after zinc deprivation for three days.…”
Section: Discussionmentioning
confidence: 99%
“…Male Balb/c 50 (C) 18 mg as zinc sulphate Increased mean survival (40) 50 (Z) C57Bl/6 mice 8 (C) 300 mg/kg of Zn for 25 d Improved thymic output (47) 8 (Z) Table 1) in the majority of the studies, Prasad et al (49) and Boukaiba et al (50) have found an increment of thymulin activity and improvement in response to skin-test antigens and taste acuity; Bogden et al (51) have reported some benefit exclusively for increased lymphocyte mitogen proliferative response; Cakman et al (52) have found enhanced IFN-g production by leucocytes; Fortes et al (53) report an increased number of cytotoxic T lymphocytes; Hodkinson et al (54) describe no effect on some markers of immunity (natural killer cells) or inflammation (C-reactive protein), but only increased the ratio of CD4/CD8 T lymphocytes at month 6; Kahmann et al (55) report reduced levels of activated T-cells and basal IL-6 release from peripheral blood mononuclear cells and improved T-cell response. Using higher doses of zinc, 40-220 mg/d with different lengths of treatment (Table 1), Duchateau et al (56) and Sandstead et al (57) have observed an improvement in response to skin-test antigens and taste acuity; an improved delayed type hypersensitivity reaction has been also found in a limited number of subjects by Cossack (58) and by Wagner et al (59) ; Prasad et al (60) found improved IL-2 mRNA.…”
Section: (Z)mentioning
confidence: 99%